Silver powder with uniform internal pores and nano-particles growing on surface and preparation method of silver powder
By controlling the reaction conditions and additives, silver powder with uniform particle size and uniform internal pores were prepared, which solved the performance problems caused by uneven pores during the sintering process of existing silver powder, and achieved efficient sintering performance and simplified process flow.
Patent Information
- Application Number
- CN202411892688.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
During the sintering process, the silver wire shrinks and collapses excessively due to uneven holes, the product pass rate is low, the service life is short, and the sintering process is complicated, which is not conducive to industrial production.
By controlling the pH value of the reactants, the order of addition, etc., the reaction speed is controlled, and the size of silver ion grain clusters is controlled, the pores within the silver powder are uniform, and nanoparticles are grown on the surface to prepare silver powder with uniform particle size and uniform internal pores.
The particle size uniformity and internal pore uniformity of silver powder are achieved, the sintering performance of silver wire is improved, the high tap density and wide sintering temperature window are maintained, the product pass rate and service life are improved, and the sintering process is simplified.
Smart Images

Figure CN119703107A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a silver powder with uniform internal pores and surface-grown nanoparticles and a preparation method thereof. Background Art
[0002] With the rapid development of production technologies such as precision photovoltaic narrow line width printing and laser sintering, the requirements for the printability and fast sintering performance of silver paste are getting higher and higher. As the main raw material of silver paste, the particle size distribution, internal structure and micro-morphology of silver powder are particularly important for the printability and fast sintering performance of silver paste.
[0003] Hollow structure polycrystalline silver powder, due to its special spatial structure, is conducive to reducing the silver content in photovoltaic silver paste and achieving the purpose of reducing costs. However, the hollow holes in the middle of the silver powder on the market are single, the holes are too large, and the pores are uneven. During the sintering process, it is easy to cause excessive shrinkage and collapse of the silver wire, resulting in low product qualification rate and short service life. In addition, the sintering process is complicated, which is not conducive to industrial production. Summary of the invention
[0004] The object of the present invention is to provide a silver powder with uniform internal pores and surface-grown nanoparticles, the silver powder has good particle size uniformity, a particle size distribution of 0.7-0.8, and uniform internal pores.
[0005] Another object of the present invention is to provide a method for preparing silver powder with uniform internal pores and surface-grown nanoparticles, by controlling the pH value of the reactants, the order of addition, etc. to control the reaction rate, thereby controlling the size of the silver ion grain clusters and controlling the uniformity of the internal pores of the silver powder.
[0006] The present invention solves the technical problem by adopting the following technical solutions.
[0007] On the one hand, an embodiment of the present invention provides a method for preparing a silver powder with uniform internal pores and surface-grown nanoparticles, comprising the following steps:
[0008] S1, prepare silver nitrate solution;
[0009] S2, prepare the base solution: add the reducing agent and dispersant to the deionized water and stir evenly; then add alkali solution to adjust the pH value to 3-7;
[0010] S3, preparing a reducing solution: adding a reducing agent to deionized water, stirring evenly, and then adding an appropriate amount of ammonia water or sodium hydroxide to control the pH of the solution to 3.0-8.0;
[0011] S4, preparing secondary reaction additives: adding soluble halogen metal sodium salt or potassium salt to ammonia water, stirring and mixing evenly; wherein the soluble halogen metal sodium salt or potassium salt can be metal salts such as NaCl, KCl, NaBr, KBr, etc.
[0012] S5, adding the silver nitrate solution and the reducing solution to the base solution for the first time, and mixing them evenly; adding the secondary reaction additive, and mixing them evenly; and adding the remaining silver nitrate solution and the reducing solution for the second time, and mixing them evenly;
[0013] S6, adding a coating agent, mixing evenly to carry out coating reaction, and after the coating reaction is completed, performing solid-liquid separation, drying, and pulverizing to obtain the silver powder.
[0014] In some embodiments of the present invention, in step S1, the step of preparing the silver nitrate solution is: dissolving the silver nitrate crystals in deionized water, stirring evenly, and storing at a temperature of 20-30° C. for standby use, wherein the mass fraction of the silver nitrate solution is 20-30wt%.
[0015] In some embodiments of the present invention, in step S2, the reducing agent is one or a mixture of ascorbic acid, sodium ascorbate, or both; the dispersant is one or more of PVPK30 (polyvinyl pyrrolidone K30), PVPK60 (polyvinyl pyrrolidone K60), gelatin, gum arabic, polyethylene glycol, and polyvinyl alcohol.
[0016] In some embodiments of the present invention, in step S2, the mass fraction of the reducing agent in the base liquid is 1.0-4.2 wt %, and the mass fraction of the dispersant in the base liquid is 1.0-3.0 wt %.
[0017] In some embodiments of the present invention, in step S3, the reducing agent is ascorbic acid, sodium ascorbate or a mixture of the two, and the mass fraction of the reducing agent in the reducing agent solution is 8.0-10%wt.
[0018] In some embodiments of the present invention, in step S5, the volumes of the silver nitrate solution and the reducing solution added for the first time are 75-98% of the total amount, respectively, and the addition is completed within 4-8 minutes.
[0019] In some embodiments of the present invention, in step S5, the volumes of the silver nitrate solution and the reducing solution added for the first time are 95% of the total amount thereof.
[0020] In some embodiments of the present invention, in step S6, the coating agent is one of stearic acid, lauric acid, myristic acid, and oleic acid.
[0021] In some embodiments of the present invention, in step S6, the mass of the coating agent added is 0.1-1% of the mass of the silver nitrate.
[0022] On the other hand, an embodiment of the present invention provides a silver powder with uniform internal pores and nanoparticles grown on the surface, which is prepared by the above preparation method.
[0023] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:
[0024] The silver powder prepared by the preparation method provided by the present invention has the characteristics of good particle size uniformity, the particle size distribution is 0.7-0.8, and the particles are uniform; the silver powder has relatively uniform pores inside, so that the silver powder can maintain its high tap density performance and reduce the sintering temperature of the silver powder, and the silver wire can maintain a good linear shape after rapid sintering. There are controllable numbers of nano silver particles on the surface of the silver powder particles, which makes it easier to generate sintering necks during the sintering process of the silver powder, has higher sintering activity, and after being configured into silver paste, the sintering temperature window of the silver paste is wider.
[0025] The preparation method provided by the present invention controls the redox rate of silver nitrate to obtain a silver powder containing internal pores, wherein the internal pores are uniform in size and the porosity is between 2% and 5%. The tap density is not affected and the aspect ratio of the linear shape during the sintering process of the silver wire can be effectively maintained. Secondly, a secondary reaction additive is added to the reaction system, and the pH value of the silver powder precursor solution in the previous step is readjusted and the particle size is controlled through a secondary reaction, and the redox reaction is re-performed to further attach nanosilver particles to the surface of the silver powder particles. The silver powder particles have a size of 1.0-2.0 μm and a uniform particle size distribution. The tap density of the silver powder is ≥5.8 g / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 This is an electron microscope image of the cross section of the silver powder in Example 1 of the present invention;
[0028] Figure 2 This is an electron microscope image of the silver powder cross section of Example 3;
[0029] Figure 3 This is an electron microscope image of the silver powder cross section of Example 4;
[0030] Figure 4This is the electron microscope image of the silver powder in Example 2;
[0031] Figure 5 This is the electron microscope image of the silver powder in Example 4;
[0032] Figure 6 This is the electron microscope image of the silver powder in Example 5. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to specific embodiments.
[0035] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0036] Example 1
[0037] The silver powder of this embodiment is prepared according to the following steps:
[0038] S1. Preparation of oxidation solution: Add silver nitrate crystals into pure water to dissolve and prepare a solution with a concentration of 30%wt, wherein the conductivity of pure water is required to be 1.5μm / cm, and the temperature after dissolution is controlled at 25±1℃.
[0039] S2, base liquid preparation: add 30L of pure water to the reactor, then add the reducing agent (vitamin C, which is industrial grade Vc that can be purchased on the market) and the dispersant (PVPK30, which is PVP that can be purchased on the market), respectively, keep the stirring speed at 300r / min, stir for 30 minutes to mix evenly, and control the temperature at 25±1°C, then add appropriate amount of ammonia water to control the pH of the mixed solution between 3.0-4.0, wherein the mass fraction of the reducing agent in the base liquid is 2.5%wt, and the mass fraction of the dispersant is 3.0%wt;
[0040] S3, reducing solution preparation: add vitamin C to deionized water, stir evenly, prepare a vitamin C solution with a mass fraction of 10% wt, add an appropriate amount of sodium hydroxide, and control the solution pH between 3-4;
[0041] S4. Preparation of secondary reaction additives: Measure 800 ml of 25% ammonia water, add 0.2 g of NaCl and dissolve it in the ammonia water for later use;
[0042] S5, oxidation-reduction reaction: keep the temperature of the bottom liquid of the reactor of S2 constant at 25±1℃ and the stirring speed at 300r / min. After it is fully dissolved, stop controlling the temperature. Add the oxidizing solution prepared by S1 and the reducing solution prepared by S3 to the bottom liquid of the reactor at the same time. When 95% of the total weight of the oxidizing solution is added (i.e. the first addition), stop adding the oxidizing solution and the reducing solution. The addition time is controlled to be 8min. Then pour the secondary reaction additives prepared by S4 into the bottom liquid of the reactor, and then add the remaining oxidizing solution and reducing solution to the bottom liquid at the same flow rate (the second addition);
[0043] S6. After the addition is completed, a coating agent (stearic acid) is added to the reactor. The amount of the coating agent added is 1% of the mass of silver nitrate. The coating time is controlled at 20 minutes. Then the material is discharged and the silver powder is obtained through post-treatment such as centrifugation, drying, and crushing.
[0044] Example 2
[0045] The difference from Example 1 is that in this Example 2, in step S2, the pH value of the base solution is controlled at 4-5; in step S3, the pH value of the reducing solution is controlled at 5-6; in step S5, the amount of the oxidizing solution added for the first time is 88%, and the amount of the oxidizing solution added for the second time is 12%. The rest of the experimental conditions, parameters and raw materials are the same as those in Example 1.
[0046] Example 3
[0047] The difference from Example 1 is that in this Example 3, in step S2, the pH value of the base solution is controlled at 5-7; in step S3, the pH value of the reducing solution is controlled at 7-8, and the remaining experimental conditions, parameters and raw materials are the same as those in Example 1.
[0048] Example 4
[0049] The difference from Example 1 is that in this Example 4, in step S2, the pH value of the base solution is controlled at 4-5; in step S3, the pH value of the reducing solution is controlled at 5-6; the remaining experimental conditions, parameters and raw materials are the same as those in Example 1.
[0050] Example 5
[0051] The difference from Example 1 is that in this Example 5, in step S2, the pH value of the base solution is controlled at 4-5; in step S3, the pH value of the reducing solution is controlled at 5-6; in step S5, the amount of oxidizing solution added for the first time is 80%, and the amount of oxidizing solution added for the second time is 20%. The remaining experimental conditions, parameters and raw materials are the same as those in Example 1.
[0052] Example 6
[0053] The silver powder of this embodiment is prepared according to the following steps:
[0054] S1. Preparation of oxidation solution: Add silver nitrate crystals into pure water to dissolve, and prepare a solution with a concentration of 25%wt, wherein the conductivity of pure water is required to be 1.5μm / cm, and the temperature after dissolution is controlled at 25±1℃.
[0055] S2, base liquid preparation: add 30L of pure water to the reactor, then add the reducing agent (vitamin C, which is industrial grade Vc that can be purchased on the market) and the dispersant (PVPK30, which is PVP that can be purchased on the market), respectively, keep the stirring speed at 300r / min, stir for 30 minutes to mix evenly, and control the temperature at 25±1°C, then add appropriate amount of ammonia water to control the pH of the mixed solution between 3.0-4.0, wherein the mass fraction of the reducing agent in the base liquid is 2%wt, and the mass fraction of the dispersant is 2%wt;
[0056] S3, reducing solution preparation: prepare a vitamin C solution with a mass fraction of 8% wt, add an appropriate amount of ammonia water, and control the solution pH between 3.0-4.0;
[0057] S4. Preparation of secondary reaction additives: Measure 800 ml of 25% ammonia water, add 0.2 g of NaCl and dissolve it in the ammonia water for later use;
[0058] S5, oxidation-reduction reaction: keep the temperature of the bottom liquid of the reactor of S2 at 25±1℃ and the stirring speed at 300r / min. After it is fully dissolved, stop controlling the temperature. Add the oxidizing solution prepared by S1 and the reducing solution prepared by S3 to the bottom liquid of the reactor at the same time. When 75% of the total weight of the oxidizing solution is added (i.e. the first addition), stop adding the oxidizing solution and the reducing solution. The addition time is controlled to be 8min. Then pour the secondary reaction additives prepared by S4 into the bottom liquid of the reactor, and then add the remaining oxidizing solution and reducing solution to the bottom liquid at the same flow rate (the second addition);
[0059] S6. After the addition is completed, a coating agent (stearic acid) is added to the reactor. The amount of the coating agent added is 0.5% of the mass of silver nitrate. The coating time is controlled at 15 minutes. Then the material is discharged and the silver powder is obtained through post-treatment such as centrifugation, drying, and crushing.
[0060] Example 7
[0061] The silver powder of this embodiment is prepared according to the following steps:
[0062] S1. Preparation of oxidation solution: Add silver nitrate crystals into pure water to dissolve and prepare a solution with a concentration of 20%wt, wherein the conductivity of pure water is required to be 1.5μm / cm, and the temperature after dissolution is controlled at 25±1℃.
[0063] S2, base liquid preparation: add 300L of pure water to the reactor, then add the reducing agent (vitamin C, which is industrial grade Vc that can be purchased on the market) and the dispersant (PVPK30, which is PVP that can be purchased on the market), respectively, keep the stirring speed at 300r / min, stir for 30 minutes to mix evenly, and control the temperature at 25±1°C, then add appropriate amount of ammonia water to control the pH of the mixed solution between 3.0-4.0, wherein the mass fraction of the reducing agent in the base liquid is 1%wt, and the mass fraction of the dispersant is 1.5%wt;
[0064] S3, reducing solution preparation: prepare a sodium ascorbate solution with a mass fraction of 9% wt, add an appropriate amount of ammonia water, and control the solution pH between 3.0-4.0;
[0065] S4, secondary reaction additive preparation: measure 800ml of 25% ammonia water, add 0.2g KCl and dissolve it in the ammonia water, and set aside;
[0066] S5, oxidation-reduction reaction: keep the temperature of the bottom liquid of the reactor in S2 constant at 25±1℃ and the stirring speed at 300r / min. Stop temperature control when the requirements are met. Add the oxidizing solution prepared in S1 and the reducing solution prepared in S3 to the bottom liquid of the reactor at the same time. When 80% of the total weight of the oxidizing solution is added (i.e. the first addition), stop adding the oxidizing solution and the reducing solution. The addition time is controlled within 8 minutes. Then pour the secondary reaction additive prepared in S4 into the bottom liquid of the reactor, and then add the remaining oxidizing solution and reducing solution to the bottom liquid at the same flow rate (the second addition);
[0067] S6. After the addition is completed, a coating agent (stearic acid) is added to the reactor. The amount of the coating agent added is 0.1% of the mass of silver nitrate. The coating time is controlled at 20 minutes. Then the material is discharged and the silver powder is obtained through post-treatment such as centrifugation, drying, and crushing.
[0068] Example 8
[0069] The silver powder of this embodiment is prepared according to the following steps:
[0070] S1. Preparation of oxidation solution: Add silver nitrate crystals into pure water to dissolve and prepare a solution with a concentration of 30%wt, wherein the conductivity of pure water is required to be 1.5μm / cm, and the temperature after dissolution is controlled at 25±1℃.
[0071] S2, base liquid preparation: add 300L of pure water to the reactor, then add the reducing agent (sodium ascorbate) and dispersant (PVPK30, which is PVP that can be purchased on the market), keep the stirring speed at 300r / min, stir for 30 minutes to mix evenly, and control the temperature at 25±1°C, then add appropriate amount of ammonia water to control the pH of the mixed solution between 3.0-4.0, wherein the mass fraction of the reducing agent in the base liquid is 1%wt, and the mass fraction of the dispersant is 2.5%wt;
[0072] S3, reducing solution preparation: prepare a sodium ascorbate solution with a mass fraction of 10%wt, add an appropriate amount of ammonia water, and control the solution pH between 3.0-4.0;
[0073] S4, secondary reaction additive preparation: measure 800ml of 25% ammonia water, add 0.2g KCl and dissolve it in the ammonia water, and set aside;
[0074] S5, oxidation-reduction reaction: keep the temperature of the bottom liquid of the reactor in S2 constant at 25±1℃ and the stirring speed at 300r / min. Stop temperature control when the requirements are met. Add the oxidizing solution prepared in S1 and the reducing solution prepared in S3 to the bottom liquid of the reactor at the same time. When 98% of the total weight of the oxidizing solution is added (i.e. the first addition), stop adding the oxidizing solution and the reducing solution. The addition time is controlled within 8 minutes. Then pour the secondary reaction additive prepared in S4 into the bottom liquid of the reactor, and then add the remaining oxidizing solution and reducing solution to the bottom liquid at the same flow rate (the second addition);
[0075] S6. After the addition is completed, a coating agent (stearic acid) is added to the reactor. The amount of the coating agent added is 0.5% of the mass of silver nitrate. The coating time is controlled at 20 minutes. Then the material is discharged and the silver powder is obtained through post-treatment such as centrifugation, drying, and crushing.
[0076] Examples 9-13
[0077] The difference from Example 1 is that some raw materials in Examples 9-13 are different from those in Example 1, as shown in Table 1. The remaining experimental conditions and parameters are the same as those in Example 1. Among them, the reducing agent in Table 1 refers to the reducing agent in step S2 and step S3, and the reducing agents in the two steps are the same.
[0078] Table 1 reducing agent Dispersants Coating agent Example 1 Vitamin C PVPK30 Stearic acid Example 9 Vitamin C gelatin Stearic acid Example 10 Sodium Ascorbate Polyethylene glycol Lauric acid Embodiment 11 Sodium Ascorbate Gum Arabic Myristic acid Example 12 Sodium Ascorbate Polyvinyl alcohol Oleic acid Embodiment 13 Vitamin C PVPK60 Lauric acid
[0079] Experimental example
[0080] The silver powders of Examples 1-5 were used as the objects to test the properties of the silver powders, and the results are shown in Table 3. The differences between Examples 1-5 are shown in Table 2.
[0081] Table 2
[0082]
[0083]
[0084] Table 3
[0085]
[0086] Combining Table 2 and Table 3, comparing the three groups of data of Experimental Example 1, Example 3 and Example 4, when ammonia water, sodium hydroxide, etc. are added to the S2 base solution and the S3 reducing solution to control the pH, the higher the pH, the faster the reaction rate, and the smaller the particle size of the obtained silver powder. At the same time, due to the faster reaction rate, the generated silver powder grain size will be smaller, the tap density will be reduced, the specific surface area will be increased, and the sintering activity will be enhanced.
[0087] Comparing the data of Example 2, Example 4 and Example 5, when the amount of silver nitrate participating in the secondary reaction increases, the amount of small nanoparticles coated on the surface of the silver powder increases, the overall tap density of the silver powder decreases, while the specific surface area increases and the sintering activity increases.
[0088] Therefore, the pH of the base solution and the reducing solution is controlled at 3-4, and the tap density of the prepared silver powder is high and the sintering performance of the silver powder is good.
[0089] (2) The cross-sections of the silver powders of Example 1 and Example 3-2 were observed. Figure 1-3 As shown. From the electron micrograph, it can be seen that when the three groups of CP electron micrographs of Example 1, Example 3 and Example 4 are compared, when ammonia water and sodium hydroxide are added to the S2 base liquid and the S3 reducing liquid to control the pH, the higher the pH, the faster the reaction speed, the more silver microcrystals are formed, and the more likely silver microcrystal clusters are to appear, resulting in larger pores in the middle of the silver powder.
[0090] From Example 4, when the pH of the system is controlled within a suitable range, the oxygen reduction reaction rate is uniform during the reaction process, the pores in the generated silver powder are evenly distributed, and the pores are uniformly and moderately sized. During the sintering process of photovoltaic silver paste, the silver powder maintains a good aspect ratio while maintaining high sintering activity, and the winding is better.
[0091] (3) Observe the surface microstructure of the silver powder in Example 2 and Example 4-3. The results are as follows: Figure 4-6 It can be seen that, from the comparison of the three groups of electron microscopes of Example 4, Experimental Example 2 and Example 5, when the amount of silver nitrate in the secondary reaction increases from 5% to 12% and 20%, the number of small nanopowders coated on the surface of the silver powder increases significantly, so the sintering activity of the silver powder can be controlled by controlling the amount of small powders.
[0092] As the line width of photovoltaic silver paste screen printing screens is getting thinner and thinner, the excessive amount of nano-powder particles on the surface of the silver powder will increase the roughness of the silver powder and the silver powder will absorb too much oil, which will increase the viscosity of the silver paste, thereby affecting the printability of the silver paste and causing the silver paste to have an increased broken grid rate during the screen printing process. Therefore, it is preferred to use a secondary reaction silver nitrate amount of less than 20%, and the silver powder obtained therefrom has the best printability.
[0093] (4) 90% of silver powder, 1% of glass powder and 10% of organic matter (including carbitol, epoxy resin or acrylic resin, ethyl cellulose, etc.) are mixed evenly with a defoamer and a three-roller machine to form a silver paste; the silver paste is printed on the photovoltaic cell substrate by a screen printer; the photovoltaic cell substrate is placed in a high-temperature sintering furnace at a sintering temperature of 750°C to form a photovoltaic cell; and finally, a HALM machine is used to test the electrical performance of the cell. The preparation of silver powder into silver paste and the preparation and implementation process of electrical performance testing all use existing common technical means, and the required materials and equipment are all conventional equipment that can be purchased on the market. The model of the equipment and the supplier of the materials have little effect on the test results, so they are not described in detail here.
[0094] Table 4 Comparison of slurry screen printing performance
[0095]
[0096] By comparing the performance data of the three groups of silver powder slurry prepared in the above-mentioned experimental examples 1, 3 and 4, when the pH value of the reaction system is increased, the oxidation-reduction rate is faster, the larger the silver crystal clusters generated, the larger the internal pores. As in the silver powder of Example 3, the sintering activity is high, but it is easy to cause excessive shrinkage during the sintering and densification of the silver wire, the aspect ratio deteriorates, and the current and efficiency of the battery cell are relatively worse. In the silver powder of Example 4, the reaction rate of the reaction system is moderately controlled, the pore size inside the silver powder is uniform, and the pore distribution is uniform. While maintaining high sintering activity and high filling, the silver powder shrinks moderately during the sintering process, the aspect ratio is good, and the current and efficiency of the silver powder are relatively improved.
[0097] Under the premise of keeping the internal uniformity of the silver powder, the performance data of the three groups of silver powder prepared slurry in the above-mentioned experimental examples 4, 2 and 5 are compared. When the amount of silver nitrate in the secondary reaction increases, the number of nanoparticles on the surface of the silver powder increases, the silver powder has a higher roughness, and the sintering activity is higher. As in the silver powder of Example 5, the surface nanoparticles are the most, the aspect ratio after screen printing is the best, and the current is more advantageous, but the slurry viscosity is too high, the printed silver line has large fluctuations, the grid line is easy to break, and there is no particularly obvious advantage in opening pressure, filling, and efficiency. The surface particles of the silver powder in Example 2 are relatively moderate, and the viscosity of the slurry increases less (within a reasonable range), which ensures the printability of the slurry while significantly improving the current, filling and efficiency of the battery cell.
[0098] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing silver powder with uniform internal pores and surface-grown nanoparticles, characterized in that: The following steps are involved: S1, prepare silver nitrate solution; S2, prepare the base solution: add the reducing agent and dispersant to the deionized water and stir evenly; then add alkali solution to adjust the pH value to 3-7; S3, preparing a reducing solution: adding a reducing agent to deionized water, stirring evenly, and then adding an appropriate amount of ammonia water or sodium hydroxide to control the pH of the solution to 3.0-8.0; S4, preparing a secondary reaction additive: adding a soluble halogen metal sodium salt or potassium salt to the ammonia water, stirring and mixing evenly; S5, adding the silver nitrate solution and the reducing solution to the base solution for the first time, and mixing them evenly; adding the secondary reaction additive, and mixing them evenly; and adding the remaining silver nitrate solution and the reducing solution for the second time, and mixing them evenly; S6, adding a coating agent, mixing evenly to carry out coating reaction, and after the coating reaction is completed, performing solid-liquid separation, drying, and pulverizing to obtain the silver powder.
2. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In step S1, the steps of preparing the silver nitrate solution are: dissolving the silver nitrate crystals in deionized water, stirring evenly, and storing at 20-30° C. for standby use, wherein the mass fraction of the silver nitrate solution is 20-30wt%.
3. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In step S2, the reducing agent is one or a mixture of ascorbic acid and sodium ascorbate; the dispersing agent is one or more of polyvinyl pyrrolidone, gelatin, gum arabic, polyethylene glycol, and polyvinyl alcohol.
4. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In the step S2, the mass fraction of the reducing agent in the base liquid is 1.0-4.2wt%, and the mass fraction of the dispersant in the base liquid is 1.0-3.0wt%.
5. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In step S3, the reducing agent is one of ascorbic acid and sodium ascorbate or a mixture of the two, and the mass fraction of the reducing agent in the reducing agent solution is 8.0-10%wt.
6. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In step S5, the volumes of the silver nitrate solution and the reducing solution added for the first time are 75-98% of the total amount, respectively, and the addition is completed within 4-8 minutes.
7. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 6, characterized in that: In step S5, the volumes of the silver nitrate solution and the reducing solution added for the first time are 95% of the total amount.
8. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In step S6, the coating agent is one of stearic acid, lauric acid, myristic acid, and oleic acid.
9. The method for preparing silver powder with uniform internal pores and surface-grown nanoparticles according to claim 1, characterized in that: In step S6, the mass of the added coating agent is 0.1-1% of the mass of the silver nitrate.
10. A silver powder, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method of preparing metal stephanoporate spherical aluminum powder
CN101318225A
Preparation method of hollow spherical silver powder
CN113369490A
Metal particle and preparation method and application thereof
CN114082938A
Hollow-structure cauliflower-like metal silver powder and preparation method
CN116833418A
Porous spherical silver powder material and preparation method thereof
CN117718470A